Conservation Hospice: A Better Metaphor for the Conservation and Care of Terminal Species - Peterson, M. Nils; Bruskotter, Jeremy T.; Rodriguez, Shari L. (Frontiers in Ecology and Evolution, 2020)
The extinction crisis creates a need to increase conservation funding, and use it more efficiently. Most conservation resources are allocated through inefficient political processes, that seem ill-equipped for dealing with the crisis. In response, conservation triage emerged as a metaphor for thinking about the optimization of resource allocation. Since triage operates primarily as a metaphor, not means for allocating resources, its metaphorical implications are of particular importance. Of particular concern, the triage metaphor justifies abandoning some species, while acquiescing to inadequate conservation funding. We argue conservation hospice provides an alternative medical metaphor for thinking about the extinction crisis. Hospice is based on the underlying principle of caring for all [species], and places particular emphasis on expected survival time, symptom burden and relief, treatments, ability to ‘stay at home’ (i.e., in-situ conservation), and maintaining support for related species and landscapes. Ultimately, application of hospice principles may be ethically obligated for a society that accepts the idea that least some organisms are intrinsically valuable and may help place emphasis on resource allocation issues without providing implicit justification for abandoning species to extinction.